Given:
The points of the exponential function are (1,12) and (-1,0.75).
The objective is to write the equation of the exponential function.
Step-by-step explanation:
The general equation of exponential is,
![y=a(b)^x\text{ . . . . . .(1),}](https://img.qammunity.org/2023/formulas/mathematics/college/3uj8qi6mf2hnmvm6cow1wfnjag2jr5cav5.png)
First, substitute (1,12) in equation (1).
![\begin{gathered} 12=a(b)^1 \\ 12=ab\text{ . . . . . .(2)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lwub570u3h7vkd99yamtvbnadt7vkbpy0g.png)
Now, substitute (-1,0.75) in equation (1).
![\begin{gathered} 0.75=a(b)^(-1) \\ 0.75=(a)/(b) \\ 0.75b=a\ldots\text{.}\mathrm{}(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gsb8ms653nmct5m8akt4ud1uiqzhps4j6y.png)
To find b:
Substitute the value of an in equation (2).
![\begin{gathered} 12=(0.75b)(b) \\ (12)/(0.75)=b^2 \\ 16=b^2 \\ \sqrt[]{16}=b \\ b=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s4tev13wuhkdffolhpbluwi90b4s6df6zl.png)
To find a:
Substitute the value of b in equation (3),
![\begin{gathered} 0.75(4)=a \\ a=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tfbqce511qf9hb5034rc0ry9br2sp9hpav.png)
To find the equation:
Substitute the value of a and b in equation (1).
![y=3(4)^x](https://img.qammunity.org/2023/formulas/mathematics/college/ry48tv3x479wsky51uwfd7c7ti084bmvv3.png)
Hence, the equation of the exponential function is y = 3(4)^x.e